2018
DOI: 10.1007/s00586-018-5625-x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid constructs pedicle screw with apical sublaminar bands versus pedicle screws only for surgical correction of adolescent idiopathic scoliosis

Abstract: The two groups offer similar curve correction without neurologic complications in the surgical treatment of AIS (Lenke 1). The use of sublaminar bands on the apex (concave side) can be a valid fixation in the presence of hypoplastic pedicle, can reduce the thoracic hypokyphosis and derotate the vertebra but had more blood loss comparing to pedicle screws alone. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A well inserted, till the vertebral body, pedicle screw has a greater moment arm that permits to apply greater corrective forces with respect to hooks. [1724] These results may be appreciated in our series; in fact, the correction of major curve improved from a mean of 47.46 ± 19.27 in G1 to 57.30 ± 24.96 in G2, when hybrid constructs were used, but better results were achieved with only screw intrumentations.…”
Section: Discussionsupporting
confidence: 50%
“…A well inserted, till the vertebral body, pedicle screw has a greater moment arm that permits to apply greater corrective forces with respect to hooks. [1724] These results may be appreciated in our series; in fact, the correction of major curve improved from a mean of 47.46 ± 19.27 in G1 to 57.30 ± 24.96 in G2, when hybrid constructs were used, but better results were achieved with only screw intrumentations.…”
Section: Discussionsupporting
confidence: 50%
“…Qi reported the total perforation rate of 7.8% in 306 TP screws from 21 AIS patients using a landmark determined by CT scan [ 25 ]. In the literature, the reported intraoperative blood loss for AIS surgery with pedicle screw instrumentation ranged from 500 to 1212 ml [ 27 32 ] and the mean operation time ranged from 146 to 378 min [ 28 , 32 34 ]. Both the average blood loss and average operation time of our cases were comparable with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggested that 15 (26.3%) patients, presenting an APEX±1 pedicle on the concave side, would sustain a fracture if a screw for the thoracic spine was inserted. For patients in whom the PS could not be inserted at the concave side of APEX±1, we might consider using hook or sublayer wiring [ 30 , 31 ]. Convex side correction with PS inserted into the convex side might also be considered a useful correction method [ 27 ].…”
Section: Discussionmentioning
confidence: 99%